Pathways of activation of the Epstein-Barr virus productive cycle - Alison J. Sinclair; Matthew Brimmell; Fergus Shanahan; Paul J. Farrell (1991)
The promoter for the 2.8-kb RNA of Epstein-Barr virus encoding BZLF1 and BRLF1 was identified and shown to be activated by both BZLF1 and BRLF1 but not by 12-O-tetradecanoylphorbol-13-acetate. Site-directed mutagenesis suggests that two binding sites for BZLF1 within the promoter contribute to the transactivation by BZLF1. The early kinetics of induction of the 2.8- and 1.0-kb RNAs encoding BZLF1 and BRLF1 in Akata cells treated with anti-immunoglobulin indicate that both RNAs appear within 60 min. The results indicate some likely pathways of activation of Epstein-Barr virus productive cycle gene expression.